Existence and Uniqueness of Generalized Solutions to a Telegraph Equation with an Integral Boundary Condition via Galerkin's Method. (9th May 2011) - Guezane-Lakoud, Assia; Dabas, Jaydev; Bahuguna, Dhirendra
Abstract : We consider a telegraph equation with nonlocal boundary conditions, and using the application of Galerkin's method we established the existence and uniqueness of a generalized solution.